Un asunto de filiación: Aproximaciones e influencias entre las obras cinematográficas de Jean Renoir y François Truffaut - Bellido Espichán, Allison Desireé (2017)
This research project focuses on the study of the thematic and stylistic relationships established in the works of the two authors.